Interview of Suresh Patel, Chemical Engineer, Kenya Association of Manufacturers, Kenya - Patel, S. (International Livestock Research Institute, 2014)
Interviews of selected participants; views from the Regional Experts Workshop on Industrial Effluents Management in East Africa held on 19-20 May 2014, Ethiopia